2015
DOI: 10.3109/14647273.2015.1076579
|View full text |Cite
|
Sign up to set email alerts
|

Decision for disclosure: The experiences of Iranian infertile couples undergoing assisted reproductive donation procedures

Abstract: Controversy surrounding disclosure among the recipients of assisted reproductive donation procedures is escalating worldwide, but little research has been conducted in this topic. The purpose of this qualitative study was to explore the experiences of infertile couples undergoing assisted reproductive donation procedures. In this exploratory qualitative study, 32 patients (nine couples and 14 women) who were candidates to use donor eggs, donor embryos or surrogacy, and 5 members of infertility treatment team i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…One of the concerns of the infertile women in this study was the tendency to hide the use of egg donation. In this regards, Hadizadeh found that egg recipients were willing to hide the use of egg donation to avoid stigma and other people's judgment (66). The results of the present study were consistent with other studies in this area and psychological counseling seems to be necessary for infertile women, especially in cases of egg donation, to resolve their concerns (67).…”
Section: Journal Of Family and Reproductive Health supporting
confidence: 89%
“…One of the concerns of the infertile women in this study was the tendency to hide the use of egg donation. In this regards, Hadizadeh found that egg recipients were willing to hide the use of egg donation to avoid stigma and other people's judgment (66). The results of the present study were consistent with other studies in this area and psychological counseling seems to be necessary for infertile women, especially in cases of egg donation, to resolve their concerns (67).…”
Section: Journal Of Family and Reproductive Health supporting
confidence: 89%
“…46 On the other hand, in the Iranian society, childbearing is very important, so that the intention of many couples of marriage is childbearing. 59 Also this study explored men’s as well as women’s experiences in the patriarchal culture of Iranian society in order to highlight the gender issues influencing the experience of infertile couples confronting treatment failure. It seems that this study could also reflect the experiences of unsuccessful infertility treatment in other countries with a similar socio-cultural context so that it might enhance the awareness of health professionals in the region regarding the world of infertile couples confronting a treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…A study suggest that Japanese infertile women avoid contact with family, relatives and friends who have not experienced infertility (Akizuki & Kai, 2008) to maintain privacy by using selective disclosure. Hadizadeh-Talasaz et al (2015) in an Iranian study discussed that the main reason for secrecy is concern over societal negative views (Hadizadeh-Talasaz et al, 2015). Also, they manage social interactions by not allowing intrusive questions and giving only general information.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, children are considering as "gift of God" and the main cause of marriage is having children among many couples, considering the prevailing social views in Iran regarding birth and parenthood (Hadizadeh-Talasaz, Roudsari, & Simbar, 2015). Indeed, social status, marital security, and fulfillment of the religious duty all depends on having children.…”
Section: Introductionmentioning
confidence: 99%